Analysis Of The Influence Of Product Quality And Promotion & Reward Programs On Customer Loyalty Through Customer Satisfaction In Gold Savings Customers At BSI: Systematic Literature Review (SLR) With Bibliometrics - Ayu Sukma Arsy Diana; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of product quality and promotion and reward programs on customer loyalty through customer satisfaction in gold savings customers at Bank Syariah Indonesia (BSI) using the Systematic Literature Review (SLR) approach combined with bibliometric analysis. This study examines scientific articles published in the 2020–2025 range from various reputable databases such as Scopus, ScienceDirect, and Google Scholar. The literature selection process is carried out using the PRISMA method to ensure the quality and relevance of articles. A total of 75 selected articles were analyzed to identify patterns of relationships between variables, research trends, and existing research gaps. The results of the study show that product quality has a significant influence on customer satisfaction, especially through the aspects of security, transparency, and ease of access to gold savings products. In addition, promotional and reward programs have been proven to increase the perception of customer value which has a positive impact on satisfaction and loyalty. Bibliometric analysis reveals an increase in research trends related to customer loyalty in the Islamic banking sector, with a primary focus on digitizing customer services and experience. These findings strengthen the role of customer satisfaction as a crucial mediating variable in building customer loyalty. This research provides theoretical implications in the development of customer loyalty models in the Islamic financial sector as well as practical implications for BSI in designing marketing strategies and improving the quality of gold savings services.